De- Westernizing Media Theory to Make Room for African Experience - Nyamnjoh, Francis B. (Popular Media, Democracy and Development in Africa, 2010)
How should one think about popular media in the African context? Should we attempt to understand and analyse the increasing proliferation of tabloids, reality television shows, pop music, websites and mobile communications through the analytical frameworks constructed by scholars in the Global North, or does Africa pose unique research questions? Is there a danger of either essentializing Africa by treating her as ‘different’, or by ignoring her specificity by approaching her media via Western theoretical constructs? The scholar wishing to understand the interface between popular media, development and democracy in contemporary African societies is faced with a complex double bind. Elsewhere (Nyamnjoh 2005: 2-3) I have argued that African worldviews and cultural values are doubly excluded from global media discourses, first by the ideology of hierarchies and boundedness of cultures, and second by cultural industries more interested in profits than the promotion of creative diversity and cultural plurality. Little attention is accorded to how Africans negotiate and navigate the various identity margins and cultural influences in their lives, in ways that are not easily reducible to simple options or straightforward choices. The consequence of rigid dichotomies or stubborn prescriptiveness based on externally induced expectations of social transformation is an idea of democracy hardly informed by popular articulations of personhood and agency in Africa, and media whose professional values and content are not in tune with the expectations of those they purport to serve. The predicament of media practitioners in such a situation, as well as those wishing to understand African media practice through media theory, is obvious: to be of real service to liberal democracy and its expectations of modernity, they must ignore alternative ideas of personhood and agency in the cultural communities within which such practices take place and of which such practitioners and, often, scholars form part. Attending to the interests of particular cultural groups as strategically essential entities risks contradicting the principles of liberal democracy and its emphasis on civic citizenship and the autonomous individual, which media practitioners in African societies are being held accountable to.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Other in South Asian Religion, Literature and Film: Perspectives on Otherism and Otherness - Dimitrova, Diana (Routledge, 2013)
This book introduces the term "otherism" and looks at the discourse of otherism and the issue of otherness in South Asian religion, literature and film. It examines cultural questions related to the human condition of being the "other," of the process of "othering" and of the representation of "otherness" and its religious, cultural and ideological implications. The book applies the perspectives of ideological criticism, theories of hybridity, orientalism, nationalism, and gender and queer studies to gain new insights into the literature, film and culture of South Asia. It looks at the different ways of interpreting "otherness" today. The book goes on to analyze the ideological implications of the creation of "otherness" with regard to religious and cultural identity and the legitimation of power, as well as how the representation of "otherness" reflects the power structures of contemporary societies in South Asia. Offering a well-thought-out reflection on important cultural questions as well as a deep insight into the study of religion and "otherness" in South Asian literature and film, this book is a pioneering project that is of interest to scholars of South Asian Studies and South Asian religions, literatures and cultures.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."--Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

De-Westernizing Film Studies - Ba, Saer Maty; Higbee, Will (Routledge, 2012)
De-Westernizing Film Studies aims to consider what form a challenge to the enduring vision of film as a medium - and film studies as a discipline - modelled on ‘Western’ ideologies, theoretical and historical frameworks, critical perspectives as well as institutional and artistic practices, might take today. The book combines a range of scholarly writing with critical reflection from filmmakers, artists & industry professionals, comprising experience and knowledge from a wide range of geographical areas, film cultures and (trans-)national perspectives. In their own ways, the contributors to this volume problematize a binary mode of thinking that continues to promote an idea of ‘the West and the rest’ in relation to questions of production, distribution, reception and representation within an artistic medium (cinema) that, as part of contemporary moving image culture, is more globalized and diversified than at any time in its history. In so doing, De-Westernizing Film Studies complicates and/or re-thinks how local, national and regional film cultures ‘connect’ globally, seeking polycentric, multi-directional, non-essentialized alternatives to Eurocentric theoretical and historical perspectives found in film as both an artistic medium and an academic field of study. The book combines a series of chapters considering a range of responses to the idea of 'de-westernizing' film studies with a series of in-depth interviews with filmmakers, scholars and critics. Contributors: Nathan Abrams, John Akomfrah, Saër Maty Bâ, Mohammed Bakrim, Olivier Barlet, Yifen Beus, Farida Benlyazid, Kuljit Bhamra, William Brown, Campbell, Jonnie Clementi-Smith, Shahab Esfandiary, Coco Fusco, Patti Gaal-Holmes, Edward George, Will Higbee, Katharina Lindner, Daniel Lindvall, Teddy E. Mattera, Sheila Petty, Anna Piva, Deborah Shaw, Rod Stoneman, Kate E. Taylor-Jones
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé